An improved seven-level switched-capacitor-based neutral-point clamped inverter - Kakar S.; Arif M.S.B.; Ayob S.M.; Nordin N.B.M.; Mekhilef S.; Seyedmahmoudian M.; Stojcevski A. (Frontiers Media S.A., 2023)
Balancing; Electric inverters; Solar panels; Solar power generation; Topology; Common mode voltage; High power; Multilevel inverter; Multilevels; Neutral-point clamped inverters; Neutralpoint-clamped (NPC); Renewable energies; Seven-level; Switched capacitor; Voltage boosting; Renewable energy resources